Ternary solubilities of anthracene in pressurized binary water/ethanol mixtures at temperatures ranging from 393 k to 473 k - Teoh, W.H.; Mammucari, R.; Foster, N.R. (2011)
Solubility measurements were conducted for (1-x) water – x ethanol mixtures at mole fractions, x = 0, 0.02, 0.03 and 0.04 of ethanol in pressurized water/ethanol system at 50 bar between 393 K and 473 K. A static equilibrium method was utilized to measure the solubilities of anthracene. Experimental data shows that the addition of a small amount of a volatile co-solvent to an aqueus mixture enhances the solubility of a hydrophobic compound. It was found that the addition of ethanol is much more effective in enhancing the solubility of anthracene at the higher temperatures. At every concentration of ethanol studied, a plot of the log of solubility of anthracene versus temperature yields a near linear plot. Thermodynamic functions of transfer from water to water/ethanol mixtures were also derived from solubility data. The free energy of transfer for anthracene was found to decrease with the increase of x; validating that anthracene is less hydrophobic as the concentration of ethanol increases. The present study extends the database for polyaromatic hydrocarbon solubilities in subcritical water system in the presence of a volatile co-solvent. It is concluded that the use of a small amount of co-solvent in a subcritical water system can expand the use of subcritical technology while maintaining relatively mild operating conditions.